Qadhaya Al-I‘Jaz Al-‘Ilmi wa At-Tafsir Al-‘Ilmi li Al-Qur’an Al-Karim - Hamza Hassan (UIN Maulana Malik Ibrahim Malang, 2019)
يحاول الباحث في هذا البحث عقد مقارنة علمية حول قضايا علمية تتعلق بكتاب الله تعالى متمثلة في إعجازه العلمي ومحاولة التفسير العلمي للآيات بين من يجيز الحديث والتفسير العلمي للآيات القرآنية والمعجزات المحتوية عليها. وأن إثباتها للبشرية هو نوع متقدم ومتطور من أساليب الدعوة إلى الله تعالى، وبيان حقيقة صحة نسبته لله تعالى. وبين من يرى أن هذا الاتجاه نوع من أنواع التهجم على رسالة القرآن الكريم ذات الطبيعة الخاصة بهداية البشر. وأن الحديث عن إعجاز القرآن الكريم وربطه بالنظريات والحقائق العلمية الحديثة هو تأويل فاسد للقرآن الكريم والحيد به عن أهدافه الأساسية التي نزل بها والمتمثلة في قوله تعالى: ﭽﭟ ﭠ ﭡ ﭢ ﭣ ﭤ ﭥ ... ﭼ الآية الإسراء: ٩This research attempts to make scientific comparisons on scientific issues related to the book of God represented in his scientific miracle and to interpret scientific verses between those who permit the scientific interpretation and interpretation of Quranic verses and the miracles that contain them. Its proof of humanity is a developed and advanced type of methods of calling to God, and to show the truth of his health to God Almighty. Among those who believe that this trend is a kind of attack on the message of the Holy Quran of the nature of human guidance. And that the talk about the miracle of the Holy Quran and linking it to theories and modern scientific facts is a corrupt interpretation of the Holy Quran and neutralize it from the basic goals that came down, which is the saying: (This Koran guides to which I do ... verse)